Performance of river buffaloes (Bubalus bubalis) from Buffalypso breed in feeding systems based on grazing: fifteen years of researches in the Instituto de Ciencia Animal - Fundora, Orlando (Cuban Journal of Agricultural Science, 2016)
The progress of researches carried out in the Instituto de Ciencia Animal were showed out, they were about productive behavior, feeding behavior, milk and carcass composition, as well as the characterization of lactation and growth curves of buffaloes from Buffalypso breed in feeding grazing systems. Values of milk production per lactation of, approximately, 800kg as average were informed. The equation that was fitted to lactation curve Yt = 1.86 + 0.03 t + 0.00003 t2 + 1.13 ln t, where t is the time in lactation days, showed maximum production values of 4.87 l.buffalo-1.day-1in the interval between 31 and 40 days. In the first 100 d, more than the half and at 200d more than 91% of the total milk production were obtained. The lactation persistence was above 4kg up to 120 d, while correlations between milk production and buffaloes post-parturition weight were not observed. The buffaloes liveweight gain showed 1.6 times higher values in comparison with cattle, and the fattening time was significantly decreased in Buffalypso animals, although they dedicated less time to grass intake, and use it more efficiently. The equations that are adjusted to the growth curve are 4.92 +18.43 (± 0.21) age, where: 3 < age (month) < 24 in males and 546.34/ (1+exp (-0.13 (± 0.003) age + 2.28 (± 0.039), where: 0 < age (month) < 43 in females. Buffaloes showed carcass yield (50.0 to 50.2%) and meat (61.6 to 62.2%) lower to those observed in cattle, but higher in meat production per time and surface unit, as consequence of the best productive behavior. It is discuss about the elements that influence in the behavior and it is suggested to carry out studies with the new crossbreeding of this specie. Key words: buffaloes, behavior, lactation curve, growth curve